Atlas of hybrid imaging of the heart, lymph nodes and musculoskeletal system : sectional anatomy for PET/CT, PET/MRI and SPECT/CT.: sectional anatomy for PET/CT, PET/MRI and SPECT/CT. Volume 3 (2022) - Leporace, Mario; Calabria, Ferdinando; Gaudio, Eugenio; Schillaci, Orazio; Ciaccio, Alfonso; Bagnato, Antonio
No abstract available